2014
DOI: 10.1152/ajpendo.00451.2013
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β hampers glucose-stimulated insulin secretion in Cohen diabetic rat islets through mitochondrial cytochromecoxidase inhibition by nitric oxide

Abstract: induces inhibition of glucose-sensitive rats (CDs) but not Cohen diabetes-resistant rats (CDr). Coppersupplemented HSD increased activity of the copper-dependent mitochondrial respiratory chain enzyme cytochrome c oxidase (COX) and reversed hyperglycemia. This study examined the mechanism by which interleukin-1␤ modulates GSIS and the role of COX in this process. We measured COX activity, ATP content, GSIS, iNOS expression, and nitrite production with and without IL-1␤, N -nitro-L-arginine, copper, or potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…We recently showed that islets isolated from CDs rats exhibited a consistent partial reduction in COX activity, ATP content and glucose stimulated insulin secretion, which could be recovered by feeding on a copper-sufficient diabetogenic-diet. These observations are supporting the involvement of COX in β-cell dysfunction in CDs rat islets [12]. …”
Section: Introductionsupporting
confidence: 83%
“…We recently showed that islets isolated from CDs rats exhibited a consistent partial reduction in COX activity, ATP content and glucose stimulated insulin secretion, which could be recovered by feeding on a copper-sufficient diabetogenic-diet. These observations are supporting the involvement of COX in β-cell dysfunction in CDs rat islets [12]. …”
Section: Introductionsupporting
confidence: 83%
“…The extent of protection provided by IL-1bAb was associated with the duration of the treatment, demonstrating pronounced protection when IL-1bAb was injected every day during the 15 days of HSD feeding and a weaker effect when IL-1bAb was given during only the first 5 days of HSD feeding. As shown in our previous studies (5)(6)(7)11,14,15) and confirmed in the current study, IL1b is the sole proinflammatory cytokine expressed by macrophages infiltrating the pancreas. An expression of other proinflammatory markers such as the chemokine MCP1 or the cytokines IL-2, IL-6, TNF-a, and IFN-g could not be detected in the infiltrating macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…IL-1b has been shown to reduce glucose-stimulated insulin secretion (GSIS) in isolated islets (4,5). In vivo studies of patients with T2DM and animal models have shown evidence of elevated IL-1b expression in the pancreas, in insulin target tissues, as well as in the circulation (1,3,4,6,7).…”
mentioning
confidence: 99%
“…This was further validated in the present study using RT-PCR ( Figure 2I). Interestingly, WesklerZangen et al confirmed that the Cohen diabetic rat, which is a genetic model of nutritionally induced diabetes, could be linked directly to reduced OxPhos [29]. The critical regulatory role of ATP production by OxPhos is underscored by the observation that the cytochrome c oxidase (Cox) activity in islets from the transgenic MKR mouse (a dominant-negative IGF-1 receptor mutation specifically in skeletal muscle) was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%